Nitrogen Dioxide, Greenhouse Gas Emissions and Transportation in Urban Areas: Lessons From the Covid-19 Pandemic - Restrepo, Carlos E. (Frontiers in Environmental Science, 2021)
Air pollutant concentrations in cities around the world are a public health concern. Transportation is a major source of air pollutants and greenhouse gases. Nitrogen dioxide (NO2), for example, is associated with respiratory disease. This policy brief explores the relationships between transportation and air quality and greenhouse gas emissions. The Covid-19 pandemic has shown how rapid changes in transportation use can result in significant decreases in NO2 concentrations. Data from New York City supports this relationship. Transportation policies aimed at reducing traffic offer an opportunity to both mitigate greenhouse gas emissions and improve air quality. The implementation of measures to rethink public space and the use of streets in response to Covid-19 also provides insights into additional policy alternative to achieve these goals.